Letter to the Editor 34(4) - Hafiz, SM; Hossain, Syed Zakir; Amin, Md Robed (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Abstract not available J Bangladesh Coll Phys Surg 2016; 34(4): 231-232